Study of Potential Drug Interactions in COVID-19 Patients with Comorbid Type 2 Diabetes Mellitus at The General Hospital in South Tangerang City, Period 2021ral Hospital in South Tangerang City - Nurmeilis; Yusroh Umami; Nurhaida; Delila Eliza (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2025)
Diabetes mellitus is one of the common comorbidities found in COVID-19 patients. The use of large amounts of medication (polypharmacy) in COVID-19 patients with comorbid diabetes mellitus can increase the possibility of drug interactions. The study aimed to determine the potential drug-drug interactions and it is the relationship with clinical outcomes in COVID-19 patients with comorbid type 2 diabetes mellitus at the General Hospital in South Tangerang City. The study was a retrospective study conducted in the hospital by using patients medical records from January-December 2021. Potential drug-drug interactions were analyzed by using the software, Medscape, and Drugs.com. The 97 patients met the inclusion and exclusion criteria. The results of the study were found in 40 patients who experience drug interactions with COVID-19 drugs and antidiabetics (58.2%), the majority of them are in moderate severity degree (78.5%), major severity degree (21.5%), with pharmacodynamic mechanism (100%). There is no significant relationship between drug interactions and clinical outcomes of patients (P>0.05). The interactions found were all pharmacodynamic, although there was no significant relationship to clinical outcomes, therapeutic monitoring was still required.